Abdominal Wall Endometriosis – Case Series (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Endometriosis is primarily a disease of pelvis. Extra pelvic endometriosis is defined, when eutrophic endometrial tissue is detected in any site other than pelvic cavity with the specification that this invasion is benign (non-neoplastic) in nature. Endometriotic lesions are usually found on the peritoneal surfaces of the reproductive organs and adjacent structures of the pelvis, but it can occur anywhere in the body. Extra pelvic endometriosis is a rare condition and it’s most common extra-pelvic location is the abdominal wall, occurring most frequently after cesarean delivery or any other abdominal surgery. Other sites are gastrointestinal tract, respiratory tract, pleura, pericardium, diaphragm and primary umbilical endometriosis. Patient’s usually present with painful mass in the abdominal wall during menstrual period, sometimes with a typical presentation, but recently incidences of scar endometriosis is increased. Two cases are presented here. To obtain a definitive diagnosis and optimal treatment for abdominal wall endometriosis, complete excision & histopathological examination are necessary. Here we presents 3 cases with umbilical endometriosis who presented between 13 to 28 years of age. Our all cases presented with a cyclical painful, abdominal mass and sometimes bleeding from umbilical mass. Also we highlight the importance of early recognition and appropriate surgical intervention to minimize morbidity and mortality from endometriosis.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 134-140